Sustainable Development for Film-Induced Tourism: From the Perspective of Value Perception - Yi, Kui; Zhu, Jing; Zeng, Yanqin; Xie, Changqing; Tu, Rungting; Zhu, Jianfei (Frontiers in Psychology, 2022)
Tourism economy has become an important component in the structure of local economy and draws attention from various researchers and practitioners. Especially the film-induced tourism has been widely proved to promote economic and cultural development. However, few studies have analyzed the inherent characteristics of economic effect and cultural effect by film-induced tourism, and limited research has studied the dynamic mechanism of sustainable development for film-induced tourism. Therefore, in this study, we explore the mutual promotions of tourism between culture and industry from the integration of culture and industry perspective. We utilize factor analysis and structural equation modeling method for empirical analysis. We created questionnaires based on our research purpose and collected 1054 valid responses. The dynamic mechanism for the sustainable development of film-induced tourism was revealed by improving the degree of integration. The analysis results supported our research hypotheses and filled the research gap mentioned above.